(untitled) (Journal of Bangladesh Institute of Planners, 2011)
Dhaka Metropolitan Development Plan (DMDP) has been prepared finally. Though, it consumed a lot of time, it is now the only widespread policy paper to control the development in DMDP area. From the experience of physical development of recent past it is evident that, some land grabbers have taken every chance to develop Dhaka city’s hinterlands most of whose were earmarked as agricultural area or flood flow zone in Structure Plan. Now we have policy paper to protect them from unrestrained development. Moreover, this plan package holds some policies up as National Environmental Policy, 1992; National Land Policy, 2001; National Agricultural Policy. 1999; National Water Policy, 1999; National Fisheries Policy, 1998 etc. Now, to ensure a healthy urban environment in Dhaka and its surroundings, government should take every step to implement it at the ground level and at the same time, will stand by the policies that government prepared formerly. Journal of Bangladesh Institute of Planners Vol. 4. Dec 2011, pp. 71 - 79